Using High Tunnels to Enhance Organic Vegetable Production in Florida: an Overview - Shufang Tian; Xin Zhao; Isaac R. Vincent; Tian Gong; Zachary T. Ray; Jesusa Legaspi; Alejandro Bolques; Timothy W. Coolong; Juan Carlos Díaz-Pérez (EDIS)
Cost-effective high tunnel systems as a protected production tool hold great potential for offering multifaceted benefits to vegetable growers in Florida beyond season extension. The adoption of high tunnels in the U.S. has been largely fueled by the NRCS High Tunnel System Initiative. Various high tunnel structures may be adapted to the Florida environment for growing high-value vegetable crops. In particular, high tunnels can help improve crop yield and quality in organic vegetable production. This article provides an overview of high tunnel structures and environment, growth of high tunnel production and the organic produce sector, major advantages of using high tunnels to enhance organic vegetable production, and challenges of high tunnel management in Florida. Some online resources for high tunnel vegetable production are provided, and future research needs are also pointed out for improving the long-term environmental and economic sustainability of high tunnel production systems.